"If You Knew Who I Really Am …". Issue 1 (2nd January 2019) - Sherman, Deborah
ABSTRACT: This paper describes the work of a White lesbian analyst with her White gay male patient who carries a secret feminine self of which he is mortifyingly ashamed. Together they discover this feminine self as the site of childhood gender trauma—for years the patient was violently and persistently bullied for not being a masculine-enough boy. To enable this patient to address his shame and find an internal space to develop an authentic gender identity, analyst and patient must take account of and process the field of the treatment room as it exists within the larger social/political field of Trump's America, in which the forces of misogyny, homophobia, gender rigidity, and racism combine to collapse any breathable space for this dyad's multiple "deviant" identities.